2014
DOI: 10.1016/j.meatsci.2013.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative characteristics of meat from young bulls fed different levels of crude glycerin

Abstract: The objective was to evaluate the fatty acid profile and qualitative characteristics of meat from young bulls fed crude glycerin. Forty-four animals with an initial live weight of 368 ± 4 kg were used in a completely randomized design, with four treatments: no glycerin or addition of 6, 12 or 18% glycerin. The animals were slaughtered with 519.5 ± 14.9 kg of live weight. The meat characteristics assessed were chemical composition, shear force, fatty acid concentration, color and lipid oxidation. The addition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 49 publications
5
38
1
Order By: Relevance
“…However, the results of this study disagree with those found by Carvalho et al (2014), who observed a decrease in the meat color components (lightness) of cattle fed with 12% and 18% crude glycerin versus those fed with 0% and 6%. This is explained by the higher level of ether extract in diets with higher amounts of crude glycerin.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…However, the results of this study disagree with those found by Carvalho et al (2014), who observed a decrease in the meat color components (lightness) of cattle fed with 12% and 18% crude glycerin versus those fed with 0% and 6%. This is explained by the higher level of ether extract in diets with higher amounts of crude glycerin.…”
Section: Resultscontrasting
confidence: 99%
“…Our results, however, agree with those published by Françozo et al (2013), Leão et al (2013), and Eiras et al (2014), who did not detect alterations in the meat color upon inclusion of crude glycerin in the cattle diets. Contrastingly, Carvalho et al (2014) found alterations in the chemical composition of the meat from cattle receiving increasing levels of crude glycerin (0%, 6%, 12%, and 18%), in which the water content decreased as the ether extract content increased. Further, the authors did not observe alterations in the ash and crude protein contents of the meat, similar to the present study.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…On the other hand, AI and TI are related to pro-and anti-atherogenic acids, and low index values correspond to higher levels of anti-atherogenic fatty acids in fat, and, consequently, a greater preventive potential against coronary heart diseases (Ulbright and Southgate, 1991). A previous study reported a similar maintenance of desaturase and elongase activities in bulls fed 18% glycerin, although the AI was reduced with increasing dietary glycerin (Carvalho et al, 2014).…”
Section: Discussionmentioning
confidence: 52%
“…Therefore, the increase in dietary energy density may also explain the gain in absolute loin weight, In regression equations "x" means "proportion of by-product silage". which may cause a more rapid fat deposition (Carvalho et al, 2014).…”
Section: Resultsmentioning
confidence: 99%